Polymorphism of the parasite lactate dehydrogenase gene from Plasmodium vivax Korean isolates - Shin, Hyun-Il (BioMed Central, 2013)
BACKGROUND: Assaying for the parasitic lactate dehydrogenase (pLDH) is widely used as a rapid diagnostic test (RDT), but the efficacy of its serological effectiveness in diagnosis, that is antibody detection ability, is not known. The genetic variation of Korean isolates was analysed, and recombinant protein pLDH was evaluated as a serodiagnostic antigen for the detection of Plasmodium vivax malaria. METHODS: Genomic DNA was purified, and the pLDH gene of P. vivax was amplified from blood samples from 20 patients. The samples came from five epidemic areas: Bucheon-si, Gimpo-si, and Paju-si of Gyeonggi Province, Gangwha-gun of Incheon metropolitan city, and Cheorwon-gun of Gangwon Province, South Korea, from 2010 to 2011. The antigenicity of the recombinant protein pLDH was tested by western blot and enzyme-linked immunosorbent assay (ELISA). RESULTS: Sequence analysis of 20 Korean isolates of P. vivax showed that the open reading frame (ORF) of 951 nucleotides encoded a deduced protein of 316 amino acids (aa). This ORF showed 100% identity with the P. vivax Belem strain (DQ060151) and P. vivax Hainan strain (FJ527750), 89.6% homology with Plasmodium falciparum FCC1_HN (DQ825436), 90.2% homology with Plasmodium berghei (AY437808), 96.8% homology with Plasmodium knowlesi (JF958130), and 90.2% homology with Plasmodium reichenowi (AB122147). A single-nucleotide polymorphism (SNP) at nucleotide 456 (T to C) was also observed in the isolate from Bucheon, but it did not change in the amino acid sequence. The expressed recombinant protein had a molecular weight of approximately 32 kDa, as analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. Of the 40 P. vivax patients, 34 (85.0%) were positive by ELISA. CONCLUSIONS: The pLDH genes of 19 isolates of P. vivax were identical, except one for SNP at nucleotide 456. This observation indicates that this gene is relatively stable. Based on these results, the relationship between antibody production against pLDH and the pattern of disease onset should be investigated further before using pLDH for serodiagnosis.